Ashes and broken brickwork of a logical theory. - Wieder, Axel John; Waelput, Wim; Roelandt, Els; Woolley, Leonard; Christie, Agatha; Bell, Gertrude; Roelstraete, dieter; Ausstellung Stuttgart. Künstlerhaus 2009-12, 12; Tentoonstelling Gent. KIOSK 2010-2, 20 (Amsterdam : ROMA Publications, 2010)
This book can be read as an inventory of the trajectory that Kriemann pursued in relation to archaeology, to the artefact, to the image of the individual at work and the idea of the desert as a symbol of the modern desire to create an empty slate, a tabula rasa. Material from Agatha Christie's photographic archives is related to photographs that Kriemann produced of the Syrian Desert and archaeological sites in Mesopotamia. Exhibitions at: Künstlerhaus, Stuttgart and KIOSK Gent.
Ausstellung December 12, 2009 - Feruary 7, 2010
Tentoonstelling February 20 - March 28, 2010
boek
Keywords: Kriemann, Susanne